Medical School Librarians Need More Training to Support their Involvement in Evidence Based Medicine Curricula - Conway, Aislinn (Evidence Based Library and Information Practice, 2016)
Objective – To describe the self-perceived role of librarians in developing evidence based medicine (EBM) curricula and identify their current and desired level of training to support these activities. Design – Multi-institutional qualitative study. Setting – Nine medical schools in Canada and the United States of America. Subjects – Nine librarians identified by medical school faculty as central to the provision of EBM training for medical students at their institution. Methods – The researchers designed a semi-structured interview schedule based on a review of the literature and their own experiences as librarians teaching EBM. The topics covered were; librarians’ perceptions of their roles in relation to the curriculum, the training required to enable them to undertake these roles, and their professional development needs. The interviews were conducted by telephone and then audio-recorded and transcribed verbatim. The authors present five main themes; curricular design, curricular deployment, curricular assessment, educational training, and professional development. Profiles were developed for each participant based on the latter two themes and from this information common characteristics were identified. Main Results – The participants described the importance of collaboration with faculty and student bodies when designing a curriculum. Information literacy instruction and specifically literature searching and forming a research question were taught by all of the participants to facilitate curricular deployment. Some of the librarians were involved or partly involved in curricular assessment activities such as formulating exam questions or providing feedback on assignments. Educational training of participants varied from informal observation to formal workshops offered by higher education institutions. All librarians indicated a willingness to partake in professional development focused on teaching and EBM. The subjects’ perceptions of their roles are supported by Dorsch and Perry’s themes of the librarian’s role in curricular design, deployment, and assessment. The educational training received by participants included formal training and experiential and self-directed learning activities. Finally, the librarians identified their professional development needs going forward. The majority of participants indicated that they would like to attend workshops run by universities or the Medical Library Association. Others wanted to invite and host guest speakers at their own institutions. Librarians identified financial restraints and geographic location as barriers to attending professional development events. Conclusion – Librarians can be actively involved in the delivery of EBM instruction in medical schools. However, they require additional educational opportunities to enable them to develop in this role. Online training could be a viable option for self-directed learning to overcome financial and geographic constraints.